Opak Abang Dance Recontruction As The Artistic Identity Of Kendal District - Anggun Ida Mawadda (JURNAL PAKARENA, 2023)
The Opak Abang dance is the official dance of Kendal Regency, the inauguration of the Opak Abang dance has changed the appearance of the packaging of the show. The Kendal government carried out the reconstruction through excavation, reinterpretation, and reactualization. This study reviews the results of the reconstruction of the Opak Abang dance as an artistic identity in Kendal Regency. The success of the recognition of the Opak Abang dance requires the collaboration of the penta-helix roles, including the government, artists, supporting communities, cultural or artists, media, and business people. The Kendal Regency Government has made efforts to introduce this dance by involving it in various festivals and events. But in fact this dance is not well known, even by the Kendal community itself. It seems that the imbalance in the roles of the penta-helix makes this dance not yet known as the artistic identity of Kendal Regency.